Statement by the Managing Director to the International Monetary and Financial Committee on the Fund's Policy Agenda. (Policy Papers; Policy Paper ;, 2011)
Since the IMFC last met, the global economic recovery has gathered strength and financial conditions have kept improving; but members continue to face multiple and diverse challenges-slow growth, high unemployment, and fiscal and financial vulnerabilities in many advanced economies; and rapid credit growth and overheating pressures in some emerging markets. Rising food and energy prices have returned, further constraining policies. Meanwhile, global imbalances show no sign of abating, and volatility in cross border financial flows and exchange rates remains high. The outlook has been further challenged recently by unpredictable shocks: the tragic events in Japan and developments across the Middle East and North Africa. The latter also contain an important lesson for policy makers, namely that the quality of growth-especially its ability to combat unacceptably high unemployment and inequality-is critical to the sustainability of growth.